A design of soft-gauge for elevator vibration analysis based on low-cost accelerometer MMA7361L and LabVIEW - Chi Nguyen Van; Lam Huong Duong; Yen Duy Dao; Thanh Ngo Phuong (Institute of Advanced Engineering and Science, 2022)
This paper presents a design of soft-gauge using the low-cost triple-axis accelerometer MMA7361L and LabVIEW software for the purpose of elevator vibration analysis with accuracy according to national standards. The 3-dimensional vibration signals measured and collected respectively by MMA7361L and NI USB6009 are fed into a soft-gauge programmed on LabVIEW to filter, then the fast Fourier transform (FFT) is applied to determine the power spectral density (PSD) and spectrogram of vibrations of filtered vibration signals. The soft-gauge also allows real-time 3-dimensional vibration data to be recorded, this data is used for analyzing later by another professional data software. Practical test results applied for the elevator of the DONGA Plaza building show quite good vibration analysis. Class 1.5 accuracy of the soft-gauge can be obtained by experimental test. This is a fairly cost-effective and inexpensive application that can be made in conditions with limited funds that cannot afford expensive accelerometers in the training of vibration measurement and analysis in high schools and vocational schools in developing countries, like Vietnam.